Morphology of the light-organ system and bioluminescent blinking in the ponyfish tribe Equulitini (Teleostei: Leiognathidae) - Michael J. Ghedotti; Jordon J. Valdez; Rene P. Martin; Emily M. Carr; John S. Sparks (PLoS ONE, 2026)
Ponyfishes in the Family Leiognathidae uniquely possess a complex bioluminescent system with an esophageal light-producing organ containing bioluminescent bacterial symbionts, a reflective gas bladder, and transparent windows through adjacent tissues that allow light emission distant from the esophageal source to produce camouflaging counterillumination and, in some species, intraspecific communication and possibly illumination of prey. Despite having bacterial light production, a type of light production that in fishes is not known to be able to be rapidly initiated and terminated, researchers have observed many species of ponyfishes rapidly blinking. The tribe Equulitini is a well diagnosed clade of sexually dimorphic ponyfishes in which males have lateral transparent windows on the body, and males of one species, Equulites elongatus, were observed in the wild to blink rapidly through their lateral windows. This group allowed us to explore bioluminescent organ anatomy in a sexually dimorphic group and describe the morphology associated with blinking. In this study we used gross anatomical, histological, and radiological methods to investigate and describe the light organ-system of ponyfishes in the Tribe Equulitini. Although previously described generally, we provide the first detailed description of the internal structure of the bioluminescent light organ in Leiognathidae, identify the esophageal homologs of the light organ’s tissues, and describe the novel mechanism for blinking. Blinking occurs when transparent longitudinal muscle that extends over the dorsal and ventral surfaces of the light organ contract or relax extending or retracting mucosal connective tissue shutters with respect to the light emitting transparent windows on the light organ. Although males have larger light organs and transparent lateral windows on their flanks, both males and females have a similar morphology and have structures consistent with the ability to blink. We also discuss variation in bioluminescent anatomy within Tribe Equulitini.